2012
DOI: 10.2147/ott.s36213
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and prognostic significance of epithelial mesenchymal transition-related protein expression in intrahepatic cholangiocarcinoma

Abstract: BackgroundThe aim of this study was to examine the patterns of expression of epithelial-mesenchymal transition (EMT)-related proteins in intrahepatic cholangiocarcinoma. The clinicopathological and prognostic value of these markers was also evaluated.MethodsWe detected the expression status of three EMT-related proteins, ie, E-cadherin, vimentin, and N-cadherin, by immunohistochemistry in consecutive intrahepatic cholangiocarcinoma specimens from 96 patients.ResultsThe frequency of loss of the epithelial marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 19 publications
2
35
0
Order By: Relevance
“…This switch operates in both types of CCA in which an up-regulation of N-cadherin expression has been observed [18,25,34,40,41]. Increasing N-cadherin expression has been associated with lower OS in both CCA subclasses [25,40] and is an independent unfavorable prognostic factor in eCCA [40].…”
Section: Disruption Of Intercellular Junctionsmentioning
confidence: 96%
See 4 more Smart Citations
“…This switch operates in both types of CCA in which an up-regulation of N-cadherin expression has been observed [18,25,34,40,41]. Increasing N-cadherin expression has been associated with lower OS in both CCA subclasses [25,40] and is an independent unfavorable prognostic factor in eCCA [40].…”
Section: Disruption Of Intercellular Junctionsmentioning
confidence: 96%
“…Several studies confirmed an aberrant staining of vimentin in CCA tumor cells while there was no staining in benign cholangiocytes [24,25,32,35,40,[48][49][50]. Vimentin expression was associated with lymph node metastasis, portal vein invasion, tumor size, pTNM stage and poorer OS and DFS [25,31,32,35,50]. In addition, vimentin was mostly detected in poorly differentiated tumor foci and a multivariate analysis demonstrated that aberrant vimentin expression is an independent adverse prognostic factor in iCCA [50].…”
Section: Intermediate Filamentsmentioning
confidence: 96%
See 3 more Smart Citations